DISTRIBUSI HARTA KEKAYAAN DALAM PERSPEKTIF ISLAM - Indaniaty Hasanah Sari; Khayriza Sinambela, Rizqa Amelia (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Distribution means moving goods from producers to consumers so that these goods can be widely distributed. Distribution in this case is the distribution of wealth that aims to improve people's welfare. The distribution of wealth at this time became a very important issue. If the distribution of wealth is not right, it will cause injustice in society which of course causes more and more people to suffer from poverty. Islam advocates to distribute wealth. Islam prescribes the distribution of wealth to be fair to everyone and not just the rich. Because the distribution of wealth is unfair and unequal will make the poor poorer. And people who are rich will get richer, which of course can lead to social inequality in society